Effect of Fertilizer Packages on Broadcast Aus Rice in Lentil-B. Aus-Blackgram Cropping Pattern in the Char Land of Pabna in Bangladesh (Bangladesh Agronomy Journal, 2018)
The experiment was conducted at Char Sadipur in the char land of Pabna during Aus rice seasons of 2014 and 2015 to determine appropriate fertilizer dose for enhancing yield of B. Aus rice var. Hashikalmi and also to increase farmers’ income in char land under High Ganges River Floodplain (AEZ-11). The experiment was laid out in a randomized complete block design with four dispersed replications. Eight fertilizer packages T1: N40P9K16S6Zn1(STB), T2: N50P9K16S6Zn1, T3: N50P11K16S6Zn1, T4: N50P9K20S6Zn1, T5: N40P11K20S6Zn1, T6: N50P11K20S6Zn1, T7: N30P7K12S4.5Zn0.75 kg ha-1 and T8: Native nutrients (control) were tested for B. Aus rice in Lentil-B. Aus- Blackgram cropping pattern. The treatment N50P11K20S6Zn1 (T6) produced maximum grain yield 2.60 t ha-1 and 2.81 t ha-1of B. Aus rice in 2014 and 2015 cropping season, respectively. The highest gross return (Tk. 61,810 ha-1 in 2014 and Tk. 72,250 ha-1 in 2015 cropping season) and gross margin (Tk. 12,214 ha-1 in 2014 and Tk. 21,550 ha-1 in 2015 cropping season) was also recorded from N50P11K20S6Zn1 (T6) and lowest from control in both the years.Bangladesh Agron. J. 2018, 21(1): 83-88